Alternative conceptions about the concept of slope in high school students of a rural area - Salgado-Beltrán, Gerardo; García-García, Javier (IE Revista de Investigación Educativa de la REDIECH, 2024)
This paper reports the results of a research whose objective was to identify alternative conceptions about the concept of slope in high school students of a rural area. A task-based interview was used to collect data from twenty-eight 12th grade students, and the thematic analysis method was used for their respective analysis. The alternative conceptions of the slope identified were: the length of a line segment, an object, a linear equation or some element of it, the value of the angle of inclination of a line, a concept proper or characteristic of lines, the distance from the x axis to a point on it, the slope of a line graphically represents a point on the cartesian plane, and the sign of the slope is determined by the sign of the semi x axis where the graph is located. These results invite us to reflect on future research to promote an improvement in learning about the concept of slope.